Diet and Exercise for FRAILty (DEFRAIL): protocol for a study to examine the effect of a novel community-based group exercise and nutritional intervention, designed to reverse frailty in older adults - Michael Harrison; Pádraig Bambrick; Niamh Phelan; Emma Grant; Ríona Mulcahy; John Cooke (BMJ Open)
Introduction Frailty refers to a multifaceted age-related loss of physiological reserve. Aside from the immediate challenges it presents, it is also associated with various adverse health outcomes. Given our ageing population, the healthcare and societal costs resulting from frailty present a significant and growing public health challenge. Rapidly accumulating evidence suggests that resistance exercise combined with protein supplementation can reverse frailty in older adults. However, translation of these findings into practice has proven difficult, due to either a lack of clarity regarding the interventions used or the use of interventions not suitable for widespread implementation. There remains an absence of evidence-based programmes suitable for delivery to frail older adults in the community.Methods and analysis This paper outlines the protocol for a study to examine the effect of a novel programme of exercise and protein supplementation. This intervention has been developed by an expert consensus group, specifically for delivery to frail older adults in a group setting in the community. The study will take the form of a within-subjects non-randomised trial. Participants will be assessed at baseline, then following an 8-week period of regular activity, then following the 8-week intervention. Frailty (according to the Fried Frailty criteria) will be the primary outcome measure, along with a range of secondary outcome measures (including physical performance measures, body mass composition, psychosocial assessments and frailty-related biomarkers). If shown to be feasible to implement and effective at reversing frailty, the Diet and Exercise for FRAILty (DEFRAIL) intervention may facilitate more widespread participation in resistance exercise for frail older adults.Ethics and dissemination This study received ethical approval from the Research Ethics committees of both the Health Service Executive South-Eastern Area and Waterford Institute of Technology. Its findings will be disseminated through journal publications, conference presentations and other forms of public engagement.Trial registration number ISRCTN46458028; Pre-results.